Correcting the direction-of-arrival (DoA) estimates of passive UHF RFID tag signals by carrier leakage cancellation using LMS adaptive filtering - De Jesus, Neon S.
This study proposes a means of correctly estimating the direction of arrival (DoA) of backscattered signals from passive ultra high frequency radio frequency identification (UHF RFID) tags. The DoA estimation is carried out by using the root-MUSIC algorithm on a two-element receive antenna array, which is realized through a RFID reader configuration involving a mono-static (Tx/Rx) antenna and an additional receive-only antenna. It is shown that accurate DoA estimation of RFID tag signals is hampered by inherent self-interference in such RFID systems, which is caused by the high power transmission of the reader leaking into the receiver through imperfect isolation. The proposed correction involves utilizing a Least Mean Square (LMS) adaptive filter to successfully suppress the carrier leakage prior to DoA estimation. For a passive tag at θ =-30°, r=3m, SNR=10dB and using 25 bits of data from tag, simulations using typical value for RFID reader parameters showed that the standard deviation of error of the estimated DoA is approximately 1.21° or equivalently, using the law of sines, a linear error distance of 0.072 meter. The standard deviation of DoA estimation error when LMS adaptive filter is not use is equal to 30° or approximately 1.5 meter. The proposed method therefore has correctly estimated the DoA of passive UHF RFID tag signals